SISTEM INFORMASI PADA MTS DARUL DA'WAH WAL IRSYAD KOTA HARAPAN KEC. MUARA SABAK TIMUR BERBASIS WEB: Information System;MTs;Visual Studio Code;MYSql;Website. - Suana, Irma; Sulaiman (LP2M Universitas Nurdin Hamzah, 2021)
Along with the development of information technology makes the computer at this time as a tool to obtain information. Therefore, with the development of this technological advancement, MTs DDI Kota Harapan needs to promote itself through an online website on the internet. research with the title